2018
DOI: 10.1111/wvn.12298
|View full text |Cite
|
Sign up to set email alerts
|

Media, Technology Use, and Attitudes: Associations With Physical and Mental Well‐Being in Youth With Implications for Evidence‐Based Practice

Abstract: Practical implications are discussed in terms of setting limits and boundaries on technology use during childhood and adolescence, and encouraging healthy eating and physical activity at home and on college campuses. Moreover, social media could be used as a platform for intervention and prevention programs to decrease BID, EDs, depression, and anxiety.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
34
1
7

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 47 publications
(43 citation statements)
references
References 53 publications
(65 reference statements)
1
34
1
7
Order By: Relevance
“…In the final sample. sixteen studies were included (n= 13168 study participants) Canan et al, 2014;Cañon Buitrago et al, 2016;Fernández-villa et al, 2015;Mabe et al, 2014;Marco et al, 2018;Quesnel et al, 2018;Rodgers et al, 2013;Simpson and Mazzeo, 2017;Zeeni et al, 2018) with a small pooled estimate effect Pearson's r=0.22 (s.e.=0.037, p<0.001) ( Figure 5).…”
Section: At Risk Eating Disordersmentioning
confidence: 99%
See 1 more Smart Citation
“…In the final sample. sixteen studies were included (n= 13168 study participants) Canan et al, 2014;Cañon Buitrago et al, 2016;Fernández-villa et al, 2015;Mabe et al, 2014;Marco et al, 2018;Quesnel et al, 2018;Rodgers et al, 2013;Simpson and Mazzeo, 2017;Zeeni et al, 2018) with a small pooled estimate effect Pearson's r=0.22 (s.e.=0.037, p<0.001) ( Figure 5).…”
Section: At Risk Eating Disordersmentioning
confidence: 99%
“…In performing meta-analysis for the body dissatisfaction domain, we identified 24 studies in scope, four of which reported data separately for males and females. Pooled estimates are reported together (all studies; n=15494) Butkowski et al, 2019;Hummel and Smith, 2015;McLean et al, 2015;Rodgers et al, 2020Rodgers et al, , 2019Rodgers et al, , 2013Simpson and Mazzeo, 2017;Terhoeven et al, 2020;Tiggemann and Miller, 2010;Xiaojing, 2017;Zeeni et al, 2018) and for males separately (Rodgers et al, 2020(Rodgers et al, , 2019Xiaojing, 2017).…”
Section: Body Dissatisfactionmentioning
confidence: 99%
“…In each graph, the "Zen" and "Stressed Out" groups are plotted on the left axes; the mean difference is plotted on a floating axis on the right as a bootstrap sampling distribution. The mean difference is depicted as a dot; the 95% confidence interval is indicated by the ends of the vertical error bar Lepp, Barkley, & Karpinski, 2014;Thomée, Eklöf, Gustafsson, Nilsson, & Hagberg, 2007;Thomée, Härenstam, & Hagberg, 2012;Thomée, 2018;Vahedi & Saiphoo, 2018;Zeeni, Doumit, Abi Kharma, & Sanchez-Ruiz, 2018), but most of these effects are small and inconsistent. A recent study by Orben and Przybylski (2019) showed that the effect size of the association between well-being and mobile phone use is very small and might be non-existent in studies with small sample sizes.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, we were also able to expand our results to show that HPD rich in BCAA also promote resilience to stress and rescue social avoidance. Associations between life-style choices including diets and psychiatric disorders have been established (Doumit et al, 2016, 2018; Mattar et al, 2019; Quirk et al, 2013; Sanchez-Ruiz et al, 2019; Zeeni et al, 2018). Previous work has implicated prolonged use of both carbohydrate-enriched diets and high fat diets in promoting depression and anxiety, but no information was available about how HPD affect social behavior (Del Rio et al, 2016; Eudave et al, 2018; Hassan et al, 2018; Santos et al, 2018; Xu et al, 2018).…”
Section: Discussionmentioning
confidence: 99%